Pharmacological Properties of Synthetic Cannabinoids, Specifics of Their Detection and Forensic Examination - O. M. Serdega (Bulletin of Kharkiv National University of Internal Affairs)
The illegal circulation of synthetic cannabinoids intensifies criminal threats and negatively impacts vulnerable segments of the population due to their specific effects on the human psychophysiological state. This article examines the historical background of the recreational use of synthetic cannabinoids and their emergence in the illicit drug market. It presents data from contemporary neurobiological studies dedicated to these compounds.